PAJAK RESTORAN SEBAGAI SUMBER PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN KARIMUN TAHUN 2012-2014 - Kinanti, Irena Ayu; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The restaurant tax potential in Karimun is large because it is more than 1 billion a year, and always increasing every year. Automatically, the contribution in increasing revenue will be increased. Therefore, the achievement of the tax revenue can still be improved by increasing the tax restaurant. This is because there are several restaurants that disobedient to pay taxes and there are also a tax payments that arrears, and there are some tax that still have not been recorded by the local departement of revenue in karimun. These problems indicate that the management of tax collection of the restaurant is not optimal. Although the report tax avenue has exceeded the target of the restaurant tax, but the fact is there are still so many tax restaurants that were unearned.The local revenue department efforts in increasing revenue of tax restaurant can be clarified into the concept of the theory of management. The findings of the study can already be deduced that the lack of plan in formulating the revenue target, the lack of human resources to manage the restaurant tax, and there is still a lack of public awareness of the importance of taxes for development.The conclusion is, the revenue in tax restaurant must be maintained and improved. The inhibiting factors can be resolved by wise so that the effort which is conducted in raising revenues by collecting restaurant tax can run well.Keywords : Restaurants Tax, Local Departement of Revenue, Revenue.